Role of Troponin-I in Predicting Length of ICU Stay in Post-Cardiac Surgery Patients: Role of Troponin-I in Predicting Length of ICU Stay - Saleem, Wardah; Hassan, Ikram; Iqbal, Fayaz; Saleem, Fatima (Pakistan Journal of Health Sciences, 2023)
The cardiac surgery procedures are associated with a release of enzyme troponin from the heart muscles. These troponin levels can be used to predict the post-operative outcomes. Objective: To find out the relationship between troponin I levels and length of ICU stay after open heart surgery. Methods: A total of 200 patients’ data were collected from January to August 2022 at the cardiac surgery department of National Institute of Cardiovascular Diseases, Karachi. The study was conducted after the approval of Ethical Research Committee. Demographic characteristics of patients, procedure details and post-operative course was taken into account for this study. The troponin I levels were sent 12 hours after the surgery and their effect on ICU stay was studied. Results: The post-operative troponin levels were divided into different sets. There were 61% patients with troponin- I levels less than 9 ng/ml, 28% patients with troponin-I levels between 9 – 18 ng/ml and 11% patients with troponin-I levels of more than 18ng/ml. There was no difference in ICU stay between patients having troponin levels < 18ng/ml. They were all stable and their ICU stay comprised of 24 hours only. Whereas, in the group of patients having troponin levels > 18 ng/ml, the ICU stay was prolonged, extending to 48 - 72 hours. Conclusions: Serum Troponin levels can be used to predict the length of ICU stay. Higher Troponin levels > 18 ng/ml are associated with a prolonged ICU stay of more than 24 hours